Synthesis and anti-Trypanosoma cruzi activity of new 3‐phenylthio-nor-β-lapachone derivatives. Issue 15 (1st August 2015) - Cardoso, Mariana F. do Carmo; Salomão, Kelly; Bombaça, Ana Cristina; da Rocha, David R.; da Silva, Fernando de C.; Cavaleiro, José A.S.; de Castro, Solange L.; Ferreira, Vitor F.
Graphical abstract: Highlights: Derivatives of nor-β-lapachone containing 3‐phenylthio groups were synthesized. The derivatives were assayed on the infective bloodstream forms of T. cruzi . Five compounds showed higher trypanocidal activity than the standard benznidazole. Compound 13b was the most potent against T. cruzi with SI = 4.23. 3‐Phenylthio compounds were in general more active than 3‐phenyamines. Abstract: We report herein a straightforward and efficient one-step reaction to prepare new nor-β-lapachone derivatives tethered with phenylthio groups at position 3 of the furan ring. We have screened the compounds on bloodstream trypomastigotes of Trypanosoma cruzi, the causative agent of Chagas disease, aimed at finding a new prototype with high trypanocidal activity. The new compounds possess a broad range of activity (IC50 /24 h from 9.2 to 182.7 μM), higher than the original quinone (391.5 μM) and four of them higher than standard drug benznidazole (103.6 μM). The most active was compound 13b (9.2 μM), being 11 times active than benznidazole and the less toxic derivative to heart muscle cells.